Pendidikan Penggunaan Media Sosial Bagi Remaja Kristen - Roy Damanik; Agripa Selly (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
This paper aims to find out the importance of education on the use of social media for the development of Christian youth. Education on the use of social media is a lesson that is poured and how to use social media with the aim of directing and providing a good lesson to the community, especially to teenagers. How to use social media well, so that social media is not used for something that is not good. Social media users, especially Christian teenagers, really need to be equipped with the right understanding through education on the use of social media, so that teenagers have wisdom in the use of social media. This research, uses a literature study research method. The results of this study indicate that there is a need for special teaching regarding education on the use of social media, especially for Christian youth in the current era of disruption. Therefore, both parents, teachers, and the church really need to actively participate in education about the use of social media for teenagers.